O trudnych relacjach etyki z ekonomią i nowym początku - Zboroń, Halina (Humaniora. Czasopismo Internetowe, 2024)
The purpose of the considerations carried out is to determine the nature of the relationship between business ethics and economics, and in particular to demonstrate that the axiological reorientation taking place in the economic sciences today opens space for overcoming differences regarding the assumptions adopted in both disciplines that characterize business practice. The author poses a key question: is it possible to see any basis for building a common or at least similar position representative of both the community of economists and business ethicists? Answering it requires, firstly, pointing out the differences in the ways of understanding economic phenomena adopted in ethics and economics; and secondly, taking into account the current state of the world and the need to adopt voluntary restrictions on the impact on the natural environment. A prerequisite for at least a partial reconciliation of the ethical and economic vision of the economy is a change of thinking in economics – the adoption of the perspective of post-growth economics and economics of restraint.